Systematic Literature Review: Students' Mathematical Literacy Ability Through the Problem Based Learning Model - Syahdania, Ana Zakia; Waluya, Stevanus Budi (Jurnal Pendidikan Matematika, 2024)
This research aims to examine several literatures related to the Problem Based Learning learning model on mathematical literacy abilities. The research method used in this research is the SLR method. Journal searches were carried out using the keywords PBL learning model and mathematical literacy skills published in the 2019-2023 period obtained with the help of the Publish or Perish application. The results of this research show that: 1) the problem-based learning model can improve students' mathematical literacy skills; 2) research related to the PBL learning model on students' mathematical literacy abilities in the 2019-2023 period tends to be mostly carried out in 2021, at junior high school level, and is a type of quantitative research.